Single-Leg Vertical Hop Test Detects Greater Limb Asymmetries Than Horizontal Hop Tests After Anterior Cruciate Ligament Reconstruction in NCAA Division 1 Collegiate Athletes - Michael J Zarro; Matthew G Stitzlein; Jason S Lee; Robert W Rowland; Vicki L Gray; Jeffrey B Taylor; Sean J Meredith; Jonathan D Packer; Christa M Nelson (International Journal of Sports Physical Therapy)
# Background